The Effect of Entrepreneurship Education, Entrepreneurial Motivation, and Self-efficacy on Entrepreneurial Interest - Aulia Nurriski; Aminah Fitri Yusnaini (Journal of Management and Digital Business, 2025)
Abstract Purpose – This study aims to obtain empirical evidence on the effect of entrepreneurship education, entrepreneurial motivation, and self-efficacy on entrepreneurial interest. Design/methodology/approach – This study uses quantitative research methods, using primary data collected from a population of 81 students at the Al Fithrah Institute Surabaya. Data analysis is conducted using Partial Least Square (PLS) software. Findings – The results of this research found that entrepreneurship education has a positive effect and a significant effect on entrepreneurial interest. Furthermore, entrepreneurial motivation has a positive effect and a significant effect on entrepreneurial interest. Last, self-efficacy has a positive effect and an insignificant effect on entrepreneurial interest. Research limitations/implications – This study focuses on entrepreneurial interest, where this study identifies each variable that is the most dominant in shaping entrepreneurial interest. In addition, this study makes an important contribution to entrepreneurship education and planning strategies for empowering future entrepreneurs.